Another one bites the dust – Two street canyons studied with magnetic biomonitoring and OSPM modelling - Limo, Jukka (Elsevier Ltd, 2025)
Urban areas form a mosaic of microenvironments and structures, such as street canyons that are susceptible to elevated levels of traffic related pollutants. Street canyons are a relevant topic in air quality research and modelling since they are prone to reduced natural ventilation and when exposed to increased traffic emissions, can pose a serious risk to public health. We applied magnetic biomonitoring using moss bags to evaluate the quality of Operational Street Pollution Model (OSPM) and to study vertical distribution of modelled particulate matter (PM), magnetic PM and heavy metal pollution in a street canyon in Turku and Helsinki, Finland. Moss bags were attached on opposite sides of the streets at 3-, 6-, 9- and 12-m heights for 44 days in late autumn. Samples were analysed for mass-specific magnetic susceptibility (χ), hysteresis parameters and elemental components. High χ values and elemental concentrations of Fe, Al, Ti, Zn, Mn, Cu and Ba were found in both street canyons. Compared to measurements with airborne magnetic PM, the OSPM model underestimated the difference in PM concentrations between the opposite street canyon faces and overestimated the dilution of PM concentrations with altitude. In Turku the results between the OSPM model and magnetic measurements were incompatible. We suspect this is due to meteorological model input data from a distant weather station, street canyon features and a high slope angle contributing to non-uniform emissions in the street canyon. We demonstrate that the moss bag technique is a versatile tool to understand the small-scale variations of concentrations in a variety of complex urban environments.